Selective Hydrochloric Acid Leaching of Zinc, Lead and Silver from Mechanically Activated Zinc Plant Residue - Turan, M. Deniz; Assemi, Shoeleh; Nadirov, Rashid K.; Karamyrzayev, Galymzhan A.; Baigenzhenov, Omirserik; Toro, Norman (Pleiades Publishing Ltd, 2022)
A solid waste from zinc production, zinc plant residue (ZPR) is a valuable resource for the recovery of zinc (Zn), lead (Pb), and silver (Ag). However, the ferritic structure of ZPR makes it difficult to leach these metals. Here, in order to increase the reactivity of the ZPR, mechanical activation using a high-energy ball mill was used. The sample mechanically activated for 15 min was subjected to two-stage leaching with the hydrochloric acid (HCl) solution. At the 1st stage, 74% of Zn was recovered from mechanically activated ZPR sample into the solution under the following conditions: 1 M HCl, 120 min leaching duration, liquid-to-solid ratio (L : S) of 4, the temperature of 25 degrees C, and a rotation speed of 600 rpm. At the 2nd stage, 56% of Pb and 53% of Ag were recovered from the leaching residue, under the following optimized conditions: 8 M HCl, 120 min leaching duration, liquid-to-solid ratio (L : S) of 20, the temperature of 25 degrees C, and a rotation speed of 600 rpm. Conceptual flow-diagram of the zinc, lead and silver selective recovery from ZPR is proposed herein.
Keywords: zinc plant residue; mechanical activation; hydrochloric acid; selective leaching